Art studio dogs : more than 50 projects and techniques for drawing, painting, and creating 25+ breeds in oil, acrylic, pencil, and more! (Art studio, 2017)
Designed for beginning artists, Art Studio: Animals combines a variety of step-by-step art projects, including drawing, painting, mixed media, and more, to help you transform your love of animals into fine art. Opening with a helpful overview of basic tools, materials, and techniques, the book then dives into more than 50 step-by-step projects to help artists get started drawing and painting animals in any medium. Love to draw? No problem. Rather paint? Got you covered. With helpful artist tips, techniques, and methods for creating animal artwork in a variety of artistic styles, the Art Studio series helps artists of any skill level find inspiration, explore different tools and materials, and have fun in the process.